Brooding rumination as a mediator in the relation between early maladaptive schemas and symptoms of depression and social anxiety in adolescents. Issue 8 (5th October 2014) - Orue, Izaskun; Calvete, Esther; Padilla, Patricia
ABSTRACT: Theory states that different cognitive constructs can be included in an integrated sequential model. This 3‐wave longitudinal study assessed whether schema domains predict brooding rumination and brooding in turn predict depression and social anxiety symptoms among adolescents. A total of 1170 adolescents ( M age = 13.44 years old, SD age = 1.30) completed measures of schema domains, brooding rumination, depression and social anxiety symptoms at baseline, 6‐ and 12‐month follow‐up (T1, T2, T3, respectively). Results revealed that the Disconnection and Rejection schema domain at T1 predicted prospective depression symptoms at T3 directly but not through brooding rumination. However, this schema domain did not predict social anxiety symptoms. The Other‐Directedness schema domain at T1 predicted social anxiety symptoms at T3 both directly and through brooding at T2. Furthermore, this schema domain also predicted depression symptoms at T3 through brooding at T2. Identifying specific schema domains and the mechanisms through which these domains predict psychological symptoms has implications for interventions with adolescents.